Uso de microondas na síntese de 5-hidroxi-5-triclorometi-4,5-diidroisoxazóis - Beck, Paulo Henrique (2002)
A series of thirteen 5-hydroxy-5-trichloromethyl-4,5- dihydroisoxazoles have been synthesized in 78–96 % yield by environmentally benign microwave induced technique involving the cyclocondensation of 4-alkoxy-1,1,1-trichloro-3-alken-2-ones [CCl3C(O)C(R2)=C(R1)OR, where R2 = H, alkyl; aryl and R=H, alkyl] with hydroxylamine using toluene as solvent. The advantages obtained by the use of microwave irradiation in relation to classical method were demonstrated.